Research and Document Management at the Faculty of Philosophy and Letters of the National University, Costa Rica: 1973-2015 - Ugalde Víquez, Aracelly (2020)
The celebration of the 40th anniversary of the Faculty of Philosophy and Letters of the Universidad Nacional, Costa Rica, was an opportune moment to analyze its contribution to the institution, to the training of professionals and to Costa Rican society. This analysis of research and the creation of knowledge generated both by academic staff and by the student population in the Faculty of Philosophy and Letters of the Universidad Nacional, corresponds to the year of creation of the University in 1973 until 2015. The data used were the original and secondary documentary sources located in the archives and libraries of this university and the reports of the Final Works of Graduation (TFG) presented by the undergraduate and graduate students. Thus, it shows the panorama of the historical and current work of the Faculty, the lines of research, the coordination between the research carried out by the professors and that of the students, as well as the relationship with the strategic plans of each of the academic units for the management of their work and with this information the potential for editorial production can be deduced. With this panorama, comparisons were made between management processes and current doubts were dispelled, such as: what are the research lines of the Faculty of Philosophy and Letters, what is the disciplinary strength that characterizes thinking in this faculty, is there a relationship between the topics studied by students and the projects of academic staff, who are the authors studied, and what are the publications that make up the documentary memory?